2011
DOI: 10.3917/her.143.0184
|View full text |Cite
|
Sign up to set email alerts
|

L'épidémie de choléra en Haïti : lecture géopolitique d'un enjeu de santé publique

Abstract: Distribution électronique Cairn.info pour La Découverte. © La Découverte. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The World Bank estimates that the earthquake caused damage representing 120% of Haiti's GDP (in Cayemittes et al, 2013, p. 2). Haiti is considered to be particularly vulnerable to earthquakes given its high population density, and that buildings have not been constructed in adherence to antiseismic norms (Guimier, 2011). Only 9 months after the earthquake, Haiti's Ministry of Public Health and Population (Le Ministère de la Santé Publique et de la Population -MSPP) reported that there was an outbreak of cholera in the Central and Artibonite departments, a disease that had not been seen in Haiti for at least the past 100 years (Bliss & Fisher, 2013).…”
Section: Research Design and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The World Bank estimates that the earthquake caused damage representing 120% of Haiti's GDP (in Cayemittes et al, 2013, p. 2). Haiti is considered to be particularly vulnerable to earthquakes given its high population density, and that buildings have not been constructed in adherence to antiseismic norms (Guimier, 2011). Only 9 months after the earthquake, Haiti's Ministry of Public Health and Population (Le Ministère de la Santé Publique et de la Population -MSPP) reported that there was an outbreak of cholera in the Central and Artibonite departments, a disease that had not been seen in Haiti for at least the past 100 years (Bliss & Fisher, 2013).…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…however, since camps are located largely in the west and Port-au-Prince, where infrastructure is already of a better quality, these interventions exacerbated existing fragmentations in coverage and poor overall decentralization (Guimier, 2011;Human Rights Watch, 2013). Remarkably, what stands out is how much leadership departments like the MSPP and DINEPA have shown in spite of their challenging environment.…”
Section: Histories Of Agricultural and Health Intervention In Haitimentioning
confidence: 99%
See 2 more Smart Citations